Case Report: Blurred Vision and Eruptive Nevi - Bilateral Diffuse Uveal Melanocytic Proliferation With Mucocutaneous Involvement in a Lung Cancer Patient - Rafei-Shamsabadi, David; Schneider, Johanna; Trefzer, Laura; Technau-Hafsi, Kristin; Meiss, Frank; Ness, Thomas (Frontiers in Oncology, 2021)
We describe a case of a 65-year old patient presenting with unusual mucocutaneous melanocytic proliferations of a Bilateral Diffuse Uveal Melanocytic Proliferation (BDUMP) imitating a multifocal melanoma in situ, which improved dramatically after plasmapheresis. The patient first presented at the dermatology department due to rapidly evolving brown and black macules on the glans penis. Further skin involvement of the perineal and perianal region, mamillae and oral mucosa was stated. Histology from a penile biopsy was compatible with a melanoma in situ. Due to the distribution pattern and elevated serum tumor marker S100B, metastatic melanoma was considered. Staging examinations using PET-CT scan however, revealed a lung tumor, later confirmed as a Non-small-cell lung cancer (NSCLC). Primary radio chemotherapy was initiated to treat NSCLC. Shortly after initiation of radio chemotherapy the patient developed massive vision impairment and a NSCLC-associated BDUMP was diagnosed which led to the correct classification of melanocytic skin lesions as mucocutaneous BDUMP manifestation. Plasmapheresis was started resulting in a rapid improvement of vision starting ten days after the first plasmapheresis. In contrast skin manifestations started to disappear with a marked delay 4 months after the last plasmapheresis cycle. This case highlights the importance of memorizing multiple rapidly progressing melanocytic skin and/or mucous membrane spots together with visual impairment as a possible paraneoplastic BDUMP that needs a fundamentally different therapeutic approach compared to multifocal melanoma in situ.